2012
DOI: 10.1111/j.1460-9592.2012.03903.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ understanding of and compliance with fasting instruction for pediatric day case surgery

Abstract: Children we believe to be fasted may not be. Parents may deliberately misrepresent the actual fasting status of their child. Adherence to fasting advice may be affected by parents' recall and understanding of fasting advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…In a recent study, noncompliance with fasting and medication guidelines constituted a major reason for surgery cancelation [16]. In another recent study, the authors even suggested that parents may deliberately misrepresent the actual fasting status of their child [17]. However, it is important to note that parental noncompliance with preoperative fasting guidelines may be caused by lack of understanding or incorrect orders of medical staff [18].…”
Section: Parental Noncompliancementioning
confidence: 95%
“…In a recent study, noncompliance with fasting and medication guidelines constituted a major reason for surgery cancelation [16]. In another recent study, the authors even suggested that parents may deliberately misrepresent the actual fasting status of their child [17]. However, it is important to note that parental noncompliance with preoperative fasting guidelines may be caused by lack of understanding or incorrect orders of medical staff [18].…”
Section: Parental Noncompliancementioning
confidence: 95%
“…These long periods of food abstention can lead to thirst and dehydration, hunger, hypoglycemia (especially children who have lower reserves of glycogen), irritability, headache and delay in coming up from anesthesia, causing unpleasant experience for these small patients 9 , 15 . In addition, 13.5% of children presenting for elective surgery are not suitable with fasting, and it is observed that most parents do not know the real cause of the need for food deprivation preoperatively - only 9% believe is due to risk of aspiration 8 . Failure to comply with the preoperative fasting guidance often results in delays and operation cancellations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It has proved difficult to take full advantage of the 2-h fasting rule. In pediatric studies of actual preoperative fasting times, the 2-h regimen for clear fluids led to as much as 21 h of fluid-fasting [5][6][7][8]9 & ,10 && ]. It seems to be exceedingly difficult to keep a large proportion of children from fasting less than 6 h, as long as the 2-h limit is strictly implemented.…”
Section: Compliance To Fasting Regimensmentioning
confidence: 99%